Bittersweet In-betweens - Jessica Nwankwo (Stimulus: A Medical Humanities Journal, 2023)
Death and loss are hardly easy processes to endure. The artwork shows a lady who is in the dying process surrounded by loved ones (husband, mother, and even her deceased child in angel form) with a physician present and draws on aspects of the stages of grief and faith and what these things look like to me. Using surrealist imagery to better tap into the metaphorical, unseen, and emotional aspects of such an experience, my piece captures what that process might look like in one specific instance in a hospital room. As scary and uncertain as the process can be, there are also elements of hope and faith in certain instances laced into the grieving process, creating an environment and experience that is laden with emotions, impactful, and intimate. Essentially, there is a depth of human emotions experienced during difficult and disheartening situations.